Revocation Mechanisms for Blockchain Applications: A Review - Vidal, Fernando Richter; Ivaki, Naghmeh; Laranjeiro, Nuno (Anais do Latin-American Symposium on Dependable Computing (LADC), 2021)
Nowadays, blockchain has been adopted by applications that are beyond cryptocurrencies. In such applications, the data generated or transactions executed are likely to be altered (revoked) due to several reasons, including business requests, legislation, or the existence of bugs. In addition, most of the data are being created by smart contracts, which, in many cases, are built by developers with non-sophisticated development tools or lacking expertise, leading to code holding residual bugs. In blockchain systems, in which immutability is one of the most critical characteristics, implementing reliable, secure, and efficient (i.e., in terms of time) revocation is a difficult challenge. This paper reviews 8 revocation mechanisms identified in current literature and discusses the applicability of each solution and associated challenges. We expect that our analysis contributes to the definition of new or improved mechanisms for transaction and data revocation in blockchain systems.